Refined study of the interaction between HIV-1 p6 late domain and ALIX - Gerlier Denis; Briant Laurence; Chazal Nathalie; Lazert Carine; Cortay Jean-Claude (Retrovirology, 2008)
Abstract The interaction between the HIV-1 p6 late budding domain and ALIX, a class E vacuolar protein sorting factor, was explored by using the yeast two-hybrid approach. We refined the ALIX binding site of p6 as being the leucine triplet repeat sequence (Lxx)4 (LYPLTSLRSLFG). Intriguingly, the deletion of the C-terminal proline-rich region of ALIX prevented detectable binding to p6. In contrast, a four-amino acid deletion in the central hinge region of p6 increased its association with ALIX as shown by its ability to bind to ALIX lacking the proline rich domain. Finally, by using a random screening approach, the minimal ALIX391–510 fragment was found to specifically interact with this p6 deletion mutant. A parallel analysis of ALIX binding to the late domain p9 from EIAV revealed that p6 and p9, which exhibit distinct ALIX binding motives, likely bind differently to ALIX. Altogether, our data support a model where the C-terminal proline-rich domain of ALIX allows the access of its binding site to p6 by alleviating a conformational constraint resulting from the presence of the central p6 hinge.